2010
DOI: 10.4065/mcp.2009.0257
|View full text |Cite
|
Sign up to set email alerts
|

68-Year-Old Woman With Chronic Cough and Recurrent Pleural Effusions

Abstract: A 68-year-old woman with a history of hypertension, paroxysmal atrial fibrillation, and liver transplant for primary sclerosing cholangitis (PSC) presented with a 2-month history of cough and shortness of breath. Her cough, which had gradually worsened, progressed to dyspnea after several feet of walking. She denied fever, chills, sick contacts, chest pain, palpitations, orthopnea, and paroxysmal nocturnal dyspnea. She had taken levofloxacin for a presumed upper respiratory tract infection with no relief and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fortunately for this case, thoracentesis, and pleural effusion analysis were performed immediately after the discovery of pleural effusion, which suggested that the cough symptoms were caused by chylothorax. We found another rare case report of chronic cough and recurrent pleural effusion ( 4 ). Similarly, in that case, the doctors performed chest radiography after excluding other common causes of cough and found pleural effusion.…”
Section: Discussionmentioning
confidence: 94%
“…Fortunately for this case, thoracentesis, and pleural effusion analysis were performed immediately after the discovery of pleural effusion, which suggested that the cough symptoms were caused by chylothorax. We found another rare case report of chronic cough and recurrent pleural effusion ( 4 ). Similarly, in that case, the doctors performed chest radiography after excluding other common causes of cough and found pleural effusion.…”
Section: Discussionmentioning
confidence: 94%